Bio-based packaging : material, environmental and economic aspects - Sapuan, S. M.; Ilyas, Rushdan Ahmad (John Wiley & Sons, Inc., 2021)
"This book focuses on biobased packaging materials as potential green materials to address environmental pollution from non-biodegradable packaging materials and reduce the dependency on petroleum-based packaging plastics for better sustainability. Divided into three sections, this book provides comprehensive coverage of biobased packaging materials. The first section of the book covers development and characterization, discussing different biobased materials, their preparation techniques and functional properties. Part two addresses environmental considerations surrounding the use of biobased packaging; while the third section considers the current market opportunities and challenges of biobased packaging materials as well as future market prospects. Topics covered include: Starch-based and protein-based packaging materials Chitin/chitosan based films for packaging applications ·Pectin based edible films for food packaging Nanocellulose composite films ·Poly(lactic) acid modified films and polyhydroxyalkanoate (PHA) films for food packaging Manufacturing of biobased packaging materials ·Environmental advantages of biobased packaging materials Reuse and recycling of biobased packaging products Life Cycle Assessment Socio-economic impact, challenges and opportunities Current market for biobased packaging materials Regulations for food packaging materials"- Resumé vydavatel
Keywords: balení potravin; obalová technika -- ekonomické aspekty; obalová technika -- environmentální aspekty; materiály; biodegradovatelné materiály; food packaging; packaging -- economic aspects; packaging -- environmental aspects; materials; biodegradable materials; elektronické knihy; kolektivní monografie; electronic books; collective monographs